2021
DOI: 10.1371/journal.pntd.0009697
|View full text |Cite
|
Sign up to set email alerts
|

The Chagas disease study landscape: A systematic review of clinical and observational antiparasitic treatment studies to assess the potential for establishing an individual participant-level data platform

Abstract: Background Chagas disease (CD), caused by the parasite Trypanosoma cruzi, affects ~6–7 million people worldwide. Significant limitations still exist in our understanding of CD. Harnessing individual participant data (IPD) from studies could support more in-depth analyses to address the many outstanding research questions. This systematic review aims to describe the characteristics and treatment practices of clinical studies in CD and assess the breadth and availability of research data for the potential establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
0
21
0
2
Order By: Relevance
“…Therefore, this paper provides a good direction for the treatment of hepatitis C and the effect of AR and its active components on hepatitis C should be explored furtherly. Chagas disease (CD) is caused by the parasite Trypanosoma cruzi , which infects approximately 6–7 million people worldwide (Maguire et al, 2021). Current research on CD has focused on the therapeutic effects of some chemical drugs and on the structural improvement of chemical drugs, such as new thiazolyl‐isatin derivatives (Freitas et al, 2021) and benznidazole‐loaded multiparticulate delivery systems (Garcia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this paper provides a good direction for the treatment of hepatitis C and the effect of AR and its active components on hepatitis C should be explored furtherly. Chagas disease (CD) is caused by the parasite Trypanosoma cruzi , which infects approximately 6–7 million people worldwide (Maguire et al, 2021). Current research on CD has focused on the therapeutic effects of some chemical drugs and on the structural improvement of chemical drugs, such as new thiazolyl‐isatin derivatives (Freitas et al, 2021) and benznidazole‐loaded multiparticulate delivery systems (Garcia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 16 studies; 3 of these were duplicate records. The reasons for excluding the other 13 [21,[47][48][49][50][51][52][53][54][55][56][57][58] are described in Appendix 5; eight of these were excluded due to study design.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…At present, there are only two nitroimidazole derivatives, BZN and nifurtimox, both of which have similar efficacy, adverse effects (AEs) and cost characteristics [19]. BZN seems to be better tolerated than nifurtimox, and most patients (77%-85%) receive BZN [20,21]. The usual recommended dose of BZN for adults in the chronic phase is 5 mg/kg/day orally, divided into two daily doses for 60 days, but it has been suggested that the effective dose might be lower [22,23].…”
Section: Introductionmentioning
confidence: 99%
“… 13 On the other hand, nifurtimox and benznidazole are the front-line antitrypanosomal against acute Chagas' disease. 14 They are trypanocidal agents, affecting mainly the circulating trypomastigotes. 15 However, the parasites' resistance together with the high toxicity of current antiprotozoal drugs has proved to be an inefficient treatment.…”
Section: Introductionmentioning
confidence: 99%